EFEKTIVITAS PENERAPAN KONSEP E-GOVERNMENT DALAM BENTUK APLIKASI ELEKTRONIK KELURAHAN PADA KELURAHAN SUNGAIBANGKONG KECAMATAN PONTIANAK KOTA KOTA PONTIANAK PROVINSI KALIMANTAN BARAT - Verdico Arief; Ade M. Yuardani (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT Effectiveness of electronic kelurahan application function in Pontianak City is a research to know how function of e-village application helps civil apparatus of state serve society at urban village level in order to develop smart city concept. This research uses the theories by Rian Van der Merwe and James Bekker, the theory is designed to evaluate and know the benefits of a website or application by assessing how the conditions of interface, navigation, content, reliability, and technical. This research uses qualitative method with case study technique, this is done in order to present the phenomenon of multi perspective description. From the results of research, basically the existence of e-kelurahan applications is very useful for the government, but not too effective, there are still problems that must be fixed, so that the future of this application can be more effective and better than before. Research results recomende to perfect e-kelurahan applications dan system. Keywords: e-kelurahan, e-government, public service